Isokinetic knee extension and vertical jumping: Are they related? - Iossifidou, A.; Baltzopoulos, V.; Giakas, G. (Journal of Sports Sciences, 2005)
The aim of this study was to examine joint power generation during a concentric knee extension isokinetic test and a squat vertical jump. The isokinetic test joint power was calculated using four different methods. Five participants performed concentric knee extensions at 0.52, 1.57, 3.14 and 5.23 rad·s-1 on a Lido isokinetic dynamometer. The squat vertical jump was performed on a Kistler force plate. Kinematic data from both tests were collected and analysed using an ELITE optoelectronic system. An inverse dynamics model was applied to measure knee joint moment in the vertical jump. Knee angular position data from the kinematic analysis in the isokinetic test were used to derive the actual knee angular velocity and acceleration, which, in turn, was used to correct the dynamometer moment for inertial effects. Power was measured as the product of angular velocity and moment at the knee joint in both tests. Significant differences (P < 0.05) were found between mean (± s) peak knee joint power in the two tests (squat vertical jump: 2255±434W; isokinetic knee extension: 771±81W). Correlation analysis revealed that there is no relationship between the peak knee joint power during the vertical jump and the slow velocity isokinetic tests. Higher isokinetic velocity tests show better relationships with the vertical jump but only if the correct method for joint power calculation is used in the isokinetic test. These findings suggest that there are important differences in muscle activation and knee joint power development that must be taken into consideration when isokinetic tests are used to predict jumping performance.